Isolation of pathogenic bacteria from the skin ulcerous symptomatic gourami (Colisa lalia) through 16S rDNA analysis - Hossain, Mosharrof (University Journal of Zoology, Rajshahi University, 2009)
Aeromonas spp infections are probably the most common bacterial disease diagnosed in cultured warm water fish. In the present study, six strains of Aeromonas spp bacteria were isolated from the gourami (Colisa lalia) by 16S rDNA sequencing analyses that are pathogenic to freshwater fish. Among them, three were under Aeromonas veronii species, two were Aeromonas sp ATCC and one was Aeromonas hydrophila. Colisa lalia usually imported in Korea from the South and South-east Asian countries for recreational purposes. However, they are playing important role as a disease vector or carriers. The infected fish of this study frequently have hemorrhages at the base of the fins or on the skin, and gross ulcerative lesions. Internal signs include, fluid in the abdomen, swollen liver and spleen, and the intestine was distended and fluid-filled. In this study, the utility of 16S rDNA sequencing was employed to isolate Aeromonas bacteria from freshwater imported fish are important to environment, veterinary, and clinical purposes. Key word: Bacteria, Colisa lalia, 16S rDNA, Aeromonas Â  doi:10.3329/ujzru.v27i0.1948 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 21-24